2015
DOI: 10.1007/s00276-015-1596-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the Adamkiewicz artery–anterior spinal artery junction

Abstract: These anatomical findings allow a planning of the neurological risk before thoracoabdominal aorta aneurysm or thoracolumbar anterior or transforaminal spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…We estimated d2 using a W task ( f ) calculated for a small disk image corresponding to the cross section of an enhanced vessel with a diameter ϕ as,Wf0.333333em=0.333333emnormalC2J1πϕfπϕf,where J 1 () is a first‐order Bessel function, and C denotes the contrast of the enhanced vessel. ϕ = 1.0 mm and C = 200 HU were used in accordance with typical diameters of the Adamkiewicz artery, which is known as an artery not easily visualized in CTA, and a minimally required attenuation of CTA, respectively …”
Section: Methodsmentioning
confidence: 99%
“…We estimated d2 using a W task ( f ) calculated for a small disk image corresponding to the cross section of an enhanced vessel with a diameter ϕ as,Wf0.333333em=0.333333emnormalC2J1πϕfπϕf,where J 1 () is a first‐order Bessel function, and C denotes the contrast of the enhanced vessel. ϕ = 1.0 mm and C = 200 HU were used in accordance with typical diameters of the Adamkiewicz artery, which is known as an artery not easily visualized in CTA, and a minimally required attenuation of CTA, respectively …”
Section: Methodsmentioning
confidence: 99%
“…[17] The artery of Adamkiewicz is found 73% of the time between T8 and T10. [12] In the present case, the penetrating injury occurred at T9-T10, which was statistically in proximity to the artery of Adamkiewicz. Prior to the endovascular deployment of the endograft, an angiogram was performed to help visualize and avoid occlusion of the artery of Adamkiewicz, as described by Kamada et al .…”
Section: Discussionmentioning
confidence: 60%
“…The treatment of proximal and distal SINE had been reported in previous clinical cases [ 6 8 ]. Some researchers had suggested that the risk of paraplegia could be significantly reduced by preserving as many intercostal arteries as possible [ 9 , 10 ]. It was worth to be considered to avoid potential complications induced by paraplegia due to the long frame coverage area [ 9 11 ].…”
Section: Discussionmentioning
confidence: 99%